Palladium-polymer nanoreactors for the aqueous asymmetric synthesis of therapeutic flavonoids. Issue 7 (30th January 2018) - Lestini, E.; Blackman, L. D.; Zammit, C. M.; Chen, T.; Williams, R. J.; Inam, M.; Couturaud, B.; O'Reilly, R. K.
Abstract : Polymeric core–shell micelles incorporating a chiral palladium pyridinooxazoline catalyst are presented as nanoreactors for the aqueous asymmetric synthesis of flavanones, a class of flavonoids, with therapeutic properties. Abstract : Polymeric core–shell micelles incorporating a chiral palladium pyridinooxazoline catalyst are presented as nanoreactors for the aqueous asymmetric synthesis of flavanones, a class of flavonoids with therapeutic properties. Use of the nanoreactor was found to increase catalyst activity, enabling catalysis at room temperature, with low palladium loadings and without any additives.